The Christmas quilt - Worth, Lenora (Worth, Lenora. Shadow Lake series, 2023)
When Matthew Mueller, the man she longs to spend her life with, returns to Shadow Lake with another woman in tow, Collette King begins a quilt to heal her broken heart but soon discovers fate and a Christmas miracle have other plans in store for her.